UJI EFEK ANTIDIARE EKSTRAK ETANOL DAUN SENDOK (Plantago mayor L.) TERHADAP MENCIT (Mus musculus) JANTAN DENGAN METODE TRANSIT INTESTINAL - Abd. Malik; Aminullah Aminullah (As-Syifaa Jurnal Farmasi, 2009)
The herb Daun sendok (Plantago mayor L.) traditionally used by people as medicine for treatment of diarrhea. The plants spread widely in south sulawesi area as decoratif herb so that is easy earning and developed as antidiarrhea medicine from natural product. The research of antidiarrhea with transit intestinal method on mices (Mus musculus). The mices is grouped by rawu method to five group. Group I is a control by NaCl fisiologis,  group II is a comparator by Loperamid-HCl, group III, IV, and V as examination each 1%, 1,5%, dan 2%. The research conclude that ekstract with concentration 2 % having activity is more potent than the loperamid-HCl, concentration 1,5% has equal activity with the loperamid-HCl and concentration 1% having below activity than the loperamid-HCl.Key words: Plantago mayor L, Antidiarrhea, Loperamid-HCl